Le corps en transformation : représentation et conception du cadavre dans la pensée aztèque - Nathalie Ragot (Ateliers d'Anthropologie)
This article offers a study of the practices and representations associated with dead bodies among the Aztec. Basing the analysis on ethnohistorical sources (codexes and chronicles), three successive points are broached: the iconographic conventions for the representation of corpses; the treatment of the body in different funeral rituals; extraordinary customs reserved for the remains of certain dead people (people who were sacrificed and woman who died giving birth).